A comparison of the commoner material culture to that of the elite material culture at Great Zimbabwe - Sonnenberg, Liesl (Department of Archaeology, 2017)
This dissertation presents the results of a study done on the area situated outside of the Outer Perimeter Wall, believed to be the commoner area at Great Zimbabwe. The methodology used in this study combined archival with artefact studies and archaeological field work. The study aimed to acquire an understanding of the uses at the commoner area at Great Zimbabwe. Focus was aimed at material culture used by the underclass to understand how it compares with that of the upper class. The comparison between the elite and non-elite areas showed that there was not a large difference between the material cultures. The ceramic analysis showed an expansion of Great Zimbabwe over time. These results are important and offer a new perspective on the social stratigraphy of the Great Zimbabwe civilization. The differences found related to objects of power, such as stone walling and soapstone artefacts; these objects only being seen in the elite areas. This study offers a new perspective in the analysis of Great Zimbabwe, and the methodology could be used as a foundation for future studies of ancient civilizations world-wide.